High anxieties : cultural studies in addiction - Brodie, Janet Farrell; Redfield, Marc, 1958- (University of California Press, 2002)
High Anxieties explores the history and ideological ramifications of the modern concept of addiction. Little more than a century old, the notions of "addict" as an identity and "addiction" as a disease of the will form part of the story of modernity.
Keywords: Substance abuse -- Social aspects.; Drugs and literature.; Drugs and motion pictures.; Alcoholism in literature.; Alcoholism in motion pictures.; Virtual reality -- Social aspects.; Polytoxicomanie -- Aspect social.; Drogues et littérature.; Drogues et cinéma.; Alcoolisme dans la littérature.; Alcoolisme au cinéma.; Réalité virtuelle -- Aspect social.; SOCIAL SCIENCE -- Customs & Traditions.; SOCIAL SCIENCE -- Sociology -- General.; Alcoholism in literature; Alcoholism in motion pictures; Drugs and literature; Drugs and motion pictures; Substance abuse -- Social aspects; Virtual reality -- Social aspects; Alcoolisme.; Aspect social.; Cinéma.; Drogue.; Polytoxicomanie.; Réalité virtuelle.; Toxicomanie.; Thème littéraire.; Thème.; Cultural studies.; Illness & addiction: social aspects.; Popular culture.; Food and Drink.